The Spatio-Temporal Distribution of Cell Wall-Associated Glycoproteins During Wood Formation in Populus - Abedi, Tayebeh; Castilleux, Romain; Nibbering, Pieter; Niittylä, Totte (Frontiers in Plant Science, 2020)
Plant cell wall associated hydroxyproline-rich glycoproteins (HRGPs) are involved in several aspects of plant growth and development, including wood formation in trees. HRGPs such as arabinogalactan proteins (AGPs), extensins (EXTs), and proline rich proteins (PRPs) are important for the development and architecture of plant cell walls. Analysis of publicly available gene expression data revealed that many HRGP encoding genes show tight spatio-temporal expression patterns in the developing wood of Populus that are indicative of specific functions during wood formation. Similar results were obtained for the expression of glycosyl transferases putatively involved in HRGP glycosylation. In situ immunolabelling of transverse wood sections using AGP and EXT antibodies revealed the cell type specificity of different epitopes. In mature wood AGP epitopes were located in xylem ray cell walls, whereas EXT epitopes were specifically observed between neighboring xylem vessels, and on the ray cell side of the vessel walls, likely in association with pits. Molecular mass and glycan analysis of AGPs and EXTs in phloem/cambium, developing xylem, and mature xylem revealed clear differences in glycan structures and size between the tissues. Separation of AGPs by agarose gel electrophoresis and staining with ß-D-glucosyl Yariv confirmed the presence of different AGP populations in phloem/cambium and xylem. These results reveal the diverse changes in HRGP-related processes that occur during wood formation at the gene expression and HRGP glycan biosynthesis levels, and relate HRGPs and glycosylation processes to the developmental processes of wood formation.